Maria Madalena e as mulheres discípulas: uma abordagem do discipulado das mulheres a partir de uma análise de Jo 20, 1-2.11-18. - Leite, Wânderson Eduardo Moraes (2020)
The performance of women in the Catholic Church has proved to be a relevant theme when it comes to approaches to women's achievements in the ecclesial environment. Although the Church has shown itself to be more open the performance of women in various sectors hitherto reserved exclusively on men, the theme needs to continue to be debated in order to promote new achievements in this context. The discipleship of women is biblical, it arises around Jesus in the same way that the discipleship of men arises, but with a differential: by welcoming women around himself, Jesus guarantees them a dignity that is a novelty until then. Women who gather around Jesus are not only listeners of their message or passive expectants, but agents as much as male disciples. This becomes evident especially in the figure of Mary Magdalene who becomes the first witness of the risen Jesus, according to the Fourth Gospel and sent by him as messenger of resurrection. The role of some women in certain narratives of the Fourth Gospel, including Mary Magdalene, is an invitation for Catholic Christian communities to rethink how women's ministry often limits for gender reasons they seek, often justify from biblical texts. Thus, Mary Magdalene and the women of the Fourth Gospel are an invitation of the Joanine community to a more discipular church formed by women and men sent equally by Jesus.